Doctoral Sojourn Experiences of Adapted Physical Education Students from Asian Countries - Takahiro Sato (Journal of International Students, 2016)
The purpose of this study was to describe and explain Asian international doctoral students’ sojourn experiences into Adapted Physical Education (APE) programs at two universities. The participants were six doctoral students from Japan, Taiwan, and South Korea. This case study was conceptualized within sojourner theory (Siu, 1952). The data sources were a demographic questionnaire and face-to-face interviews conducted during the participants’ doctoral studies. The emergent themes were (a) research challenges; (b) academic, social, and hierarchical relationships with doctoral advisors; (c) burnout; and (d) situation-specific anxiety. To better support international doctoral students, this study encourages academic departments, administrators, faculty, and all doctoral students to learn to view themselves as playing various roles including academic advisors, teachers, and graduate students.